2004
DOI: 10.1093/humrep/deh057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breastfeeding chemosignals on the human menstrual cycle

Abstract: Because compounds from lactating women and their infants modulated the ovarian cycles of women, as is seen in other mammals, they have the potential to function as pheromones, regulating fertility within groups of women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…Breastfeeding was expected to lower the ovarian cancer risk during the suppression of ovulatory cycles (Short et al, 1991, McNeilly, 2001). Chemosignals present in human milk modulate ovarian cycle length (Jacob et al, 2004). However, ovulation will resume upon supplementary feeding and reduce the intensity of breastfeeding (Short et al, 1991;Li and Qiu, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding was expected to lower the ovarian cancer risk during the suppression of ovulatory cycles (Short et al, 1991, McNeilly, 2001). Chemosignals present in human milk modulate ovarian cycle length (Jacob et al, 2004). However, ovulation will resume upon supplementary feeding and reduce the intensity of breastfeeding (Short et al, 1991;Li and Qiu, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this particular instance, however, the effect was not to synchronize but to increase variability among women. Jacob et al (2004) reported that the odors obtained from the breasts of lactating women disrupted "the normal homeostatic regulation of cycle length" in other nulliparous women who were given the chemical signals. The effect was pronounced-variability in cycles increased threefold-and was suggested to play a role in fertility in the general population of women.…”
Section: Pheromone Response: Primers Signalers Modulators and Relementioning
confidence: 99%
“…Eight entrained, OVX females implanted first with estradiol, then progesterone, and lastly a combination of the two hormones were used as odor donors during a series of phase advances, followed by a shift with clean air. Silastic capsules similar to those used in earlier experiments (20) containing crystalline estradiol benzoate (E; Sigma, St. Louis, MO) or progesterone (P; Sigma) were prepared as described in Labyak and Lee (26), with an effective length of 15 mm (DowCorning, Corning, NY; 1.98 mm ID, 3.15 mm OD). Hormone capsules were put into the odor donors for 48 h prior to their odors being routed to shifting females.…”
Section: Experiments 1: Habituation To Nonanimal Odorsmentioning
confidence: 99%
“…Subsequent studies explored the hormonal aspects of the sex difference in the use of social olfactory stimuli in reentrainment and reported that testicular hormones suppressed responsiveness to odor cues in males (21), and ovarian hormones were necessary for females responding to odor cues with accelerated reentrainment (20). Ovariectomized (OVX) females did not increase their rates of reentrainment in the presence of a social cue donor nor were they effective as donors.…”
mentioning
confidence: 99%